1981
DOI: 10.1530/acta.0.0980312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibin on rat testicular desoxyribonucleic acid (DNA) synthesis in vivo and in vitro

Abstract: Abstract. When injected in vivo 3 h before sacrifice or when incubated in vitro with testicular fragments for 3 h, tritiated thymidine, a reliable index of DNA synthesis and of mitotic activity, was incorporated into the DNA of differentiated spermatogonia, as shown by autohistoradiography. The maximum DNA specific activity was obtained in pubertal rats aged 42 days, weight 150 g. Two preparations of inhibin extracted from ram rete testis fluid (RTF) of different molecular weight (> 10 000 for RTF1 and <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…In addition, inhibin stimulated androgen secretion from theca-interstitial cells of the rat [10] and human [8] in vitro, and inhibin also enhanced LH/hCG-induced androgen synthesis when added to a newborn rat Leydig cell culture [10], while activin suppressed it [10]. These reports suggest that in both the equine fetal ovary and testis, inhibin produced from interstitial cells might play a paracrine/autocrine role in the regulation of androgen production, and inhibin produced from Sertoli cells might be suppressing spermatogonial development as reported in the rat [4,22]. Further studies to elucidate the precise roles of inhibin and/or inhibin α-subunit related molecules in equine fetal gonads are awaited.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In addition, inhibin stimulated androgen secretion from theca-interstitial cells of the rat [10] and human [8] in vitro, and inhibin also enhanced LH/hCG-induced androgen synthesis when added to a newborn rat Leydig cell culture [10], while activin suppressed it [10]. These reports suggest that in both the equine fetal ovary and testis, inhibin produced from interstitial cells might play a paracrine/autocrine role in the regulation of androgen production, and inhibin produced from Sertoli cells might be suppressing spermatogonial development as reported in the rat [4,22]. Further studies to elucidate the precise roles of inhibin and/or inhibin α-subunit related molecules in equine fetal gonads are awaited.…”
Section: Discussionsupporting
confidence: 51%
“…This does not, however, exclude the possibility that inhibin and/or inhibin α-subunit related molecules probably produced in equine fetal gonads might be functioning as paracrine/autocrine factors. The functions of inhibin within gonads has been shown by some investigators: inhibin produced from Sertoli cells during the spermatogonial development in the rat was reported to be acting as an inhibitory paracrine factor [4,22], while activin stimulated spermatogonial proliferation [11]. In addition, inhibin stimulated androgen secretion from theca-interstitial cells of the rat [10] and human [8] in vitro, and inhibin also enhanced LH/hCG-induced androgen synthesis when added to a newborn rat Leydig cell culture [10], while activin suppressed it [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, it was reported that inhibin was an endocrine hormone functioning primarily on reproductive tissues in paracrine and autocrine fashions [5,15,19]. In the testis, inhibin appeared to decrease spermatogonial mitotic activity [9,30] and to regulate Leydig cell function [11,15]. It also enhanced LH-mediated androgen production in Leydig cells [11,15].…”
Section: Animals and Tissue Preparationsmentioning
confidence: 99%
“…Ces facteurs pourraient contr61er la survie (SCF, [38]), la m u l t i p l i c a t i o n des s p e r m a t o g o n i e s (EGF/TGFa, bFGF, IGF I ; [23,30,61,64,73]), l'arr6t de la multiplication de ces cellules (TGFb, [18] ; inhibine, [16,81] de signalisation vis-a-vis des hormones (FSH, testosterone) ( Figure 3). Cependant, rexpression de ces facteurs sertoliens peut ~tre aussi sous le contrSle de facteurs locaux comme le TNFa, l'ILla ou le NGF, provenant des cellules germinales.…”
Section: S P E R M a T O G E N~s E S O U S Le Contr61e Des Facteurs Lunclassified